Ready Made Garments’ (RMG) Contribution in Women Empowerment: A Study on Bangladesh Perspective - Billah, Mohammed Masum; Manik, Md. Rafiqul Islam (European Scientific Journal, ESJ, 2017)
There is no denying the fact that without women empowerment development goals of Bangladesh is always unreachable. This country belongs to a social system where women consider as a burden for the family. However, the scenario is changing with time. Nowadays, women are working in garments sector, education sector, banking sector, different NGO’s and government organizations but the single garment sector where seventy percent of workers of 4.0 million are women and most of them are less educated, unskilled and from rural areas. These women have neither decision making power and nor access to resources before getting the job in the garments sector. The job creates ample opportunity for female workers by giving economic freedom, keeping them near the resources and facilities in the city area, and making them knowledgeable, and skills through training, counseling, and sharing problem with coworkers. The study reveals that empowerment of women vastly depends on four variables which are women’s financial contribution to family, women’s access to resources, women’s participation in household decision making and their perception of coping capacity to shocks. It has been found that garments sector significantly contribute to enhance the female worker’s ability to contribute financially, to participate in decision making, to access resources, and to cope with risks which ultimately increase their empowerment in the society as a whole.